Pengembangan Sistem Informasi Manajemen Laboratorium Berbasis Paradigma Pengguna (Studi Kasus: Fakultas Teknik Universitas Bengkulu) - Adhadi Kurniawan; Ferzha Putra Utama; Faisal Hadi (JSAI (Journal Scientific and Applied Informatics), 2021)
In the current technology era, laboratory managements require an information system. Laboratory is the core of Engineering Faculty of University of Bengkulu, but still manually in its management. This applied research’s purpose to provide laboratory information to the public and also to develop an educational management toolkit in laboratory management. This system was developed based on User Center Design (UCD). This method fully involving user in design trough their suggestion and wishes. This research had some steps are survey, analysis, data processing, system design, and implementation. The results of this study show the system is able to manage laboratory of Engineering Faculty well as indicate by the System Usability Scale (SUS) score of 76.Keywords: System, Management, Laboratory, Engineering Faculty, UCD